Java foundations : introduction to program design and data structures - Lewis, John; DePasquale, Peter;Chase, Joseph (Upper Saddle River, New Jersey : Pearson Education, 2014)
Inspired by the success of their best-selling introductory programming text, Java Software Solutions, authors Lewis, DePasquale, and Chase now release Java Foundations, Third Edition. This text is a comprehensive resource for instructors who want a two-or three-semester introduction to programming textbook that includes detail on data structures topics. Java Foundations introduces a Software Methodology early on and revisits it throughout to ensure students develop sound program development skills from the beginning. Control structures are covered before writing classes, providing a solid foundation of fundamental concepts and sophisticated topics.
1. Introduction -- 2. Data and expressions -- 3. using classes and objects -- 4. Conditionals and loops -- 5. Writing classes -- 6. Graphical User Interfaces -- 7. Arrays -- 8. Inheritance -- 9. Polymorphism -- 10. Exceptions -- 11. Analysis of algorithms -- 12. Introduction to collections: stacks -- 13. Linked structures: stacks -- 14. Queues -- 15. Lists -- 16. Iterators -- 17. Recursion -- 18. Searching and sorting -- 19. Trees -- 20. Binary search trees -- 21. Heaps and priority queues -- 22. Sets and maps -- 23. Multi-way search trees -- 24. Graphs -- 25. Databases.
Includes index.
Keywords: JAVA (COMPUITER PROGRAM LANGUAGE)